Corticosteroids in childhood epilepsies: A systematic review - Becker, Lena-Luise; Kaindl, Angela M. (Frontiers in Neurology, 2023)
Corticosteroids have been used for the treatment of patients with epilepsy for more than 6 decades, based on the hypothesis of inflammation in the genesis and/or promotion of epilepsy. We, therefore, aimed to provide a systematic overview of the use of corticosteroid regimes in childhood epilepsies in line with the PRISMA guidelines. We performed a structured literature search via PubMed and identified 160 papers with only three randomized controlled trials excluding the substantial trials on epileptic spasms. Corticosteroid regimes, duration of treatment (days to several months), and dosage protocols were highly variable in these studies. Evidence supports the use of steroids in epileptic spasms; however, there is only limited evidence for a positive effect for other epilepsy syndromes, e.g., epileptic encephalopathy with spike-and-wave activity in sleep [(D)EE-SWAS] or drug-resistant epilepsies (DREs). In (D)EE-SWAS (nine studies, 126 patients), 64% of patients showed an improvement either in the EEG or in their language/cognition following various steroid treatment regimes. In DRE (15 studies, 436 patients), a positive effect with a seizure reduction in 50% of pediatric and adult patients and seizure freedom in 15% was identified; however, no recommendation can be drawn due to the heterozygous cohort. This review highlights the immense need for controlled studies using steroids, especially in DRE, to offer patients new treatment options.